Utp14 Recruits and Activates the RNA Helicase Dhr1 To Undock U3 snoRNA from the Preribosome - Zhu, Jieyi (Mol Cell Biol, 2016)
In eukaryotic ribosome biogenesis, U3 snoRNA base pairs with the pre-rRNA to promote its processing. However, U3 must be removed to allow folding of the central pseudoknot, a key feature of the small subunit. Previously, we showed that the DEAH/RHA RNA helicase Dhr1 dislodges U3 from the pre-rRNA. DHR1 can be linked to UTP14, encoding an essential protein of the preribosome, through genetic interactions with the rRNA methyltransferase Bud23. Here, we report that Utp14 regulates Dhr1. Mutations within a discrete region of Utp14 reduced interaction with Dhr1 that correlated with reduced function of Utp14. These mutants accumulated Dhr1 and U3 in a pre-40S particle, mimicking a helicase-inactive Dhr1 mutant. This similarity in the phenotypes led us to propose that Utp14 activates Dhr1. Indeed, Utp14 formed a complex with Dhr1 and stimulated its unwinding activity in vitro. Moreover, the utp14 mutants that mimicked a catalytically inactive dhr1 mutant in vivo showed reduced stimulation of unwinding activity in vitro. Dhr1 binding to the preribosome was substantially reduced only when both Utp14 and Bud23 were depleted. Thus, Utp14 is bifunctional; together with Bud23, it is needed for stable interaction of Dhr1 with the preribosome, and Utp14 activates Dhr1 to dislodge U3.